The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1071/an20439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capsaicin supplementation on lactational and reproductive performance of Holstein cows during summer

Abstract: Context. Summer ambient temperature and humidity are major factors negatively influencing the physiology and the productive and reproductive efficiency of dairy cows. Various management and breeding approaches may be useful for maintaining productivity in dairy cows during summer to minimise these effects.Aims. The experiment was designed to test a natural phytochemical supplementation of capsaicin (CPS), followed by a specific oestrus synchronisation protocol as a means to maintain productivity and reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Future studies should review the dosage of PE, as recent studies have shown the possibility of increasing results using higher dosages [ 52 ]. The optimization of water resources in production systems is a need that can contribute to sustainability and the conscious use of water [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should review the dosage of PE, as recent studies have shown the possibility of increasing results using higher dosages [ 52 ]. The optimization of water resources in production systems is a need that can contribute to sustainability and the conscious use of water [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported significant increases in estrus response, ovulatory follicle size, ovulation rate and pregnancy rate in animals fed the capsaicin (40 mg/kg of total mixed ration daily), possibly due to capsaicin's role as a vasodilator and ability to increase blood flow to improve follicle development, meiotic maturation and embryonic development in heat stressed cows. As heat stress typically poses a negative impact on fertility, these findings support the use of capsaicin as an ameliorative strategy to improve summer breeding programs ( Abulaiti et al., 2021 ).…”
Section: Effects Of Essential Oils To Mitigate Heat Stressmentioning
confidence: 56%
“…(2013) ; Shang et al. (2016) ; Wall (2011) Capsaicin Chili Peppers milk production, rumen function, heat stress feed additive Bovine, sheep Abulaiti et al. (2021) ; McCarty et al.…”
Section: Introductionmentioning
confidence: 99%
“…The favorable impact of cinnamaldehyde in improving the rumen fermentation efficiency could be responsible for optimizing milk yield [31,32]. Additionally, in a recent study by Abulaiti, et al [33], capsaicin supplementation in Chinese Holstein dairy cows maintained milk production and composition. Furthermore, the increasing tendency in the dry-matter intake of lactating Holstein cows fed with FFS-fortified diets could also contribute to the enhancement of milk production [34].…”
Section: Discussionmentioning
confidence: 99%